Worker Protection Standard: Determining Your WPS Responsibilities - Frederick M. Fishel (EDIS)
The WPS requires agricultural employers to take steps to reduce pesticide-related risks when agricultural workers and pesticide handlers are exposed to these pesticides. The EPA has made several changes to the WPS since it was fully implemented in 1995. On November 2, 2015, the EPA revised the WPS, making significant changes to the rule’s requirements. Most of the revised provisions will become effective January 2, 2017; there are four provisions that are delayed until January 2, 2018. In late 2016, the EPA released the revised “How to Comply Manual” to provide an updated resource. This document will address determining responsibilities under the revised WPS.